Patterns of surgical complications after delayed fixation of peripartum pubic symphysis rupture: a report of 5 cases - Grzegorz Doroszewski; Jan Wasielewski; Paweł Bartosz; Adam Caban; Anna Scholz; Jerzy Białecki (Patient Safety in Surgery, 2023)
Abstract Background The disruption of the pubic symphysis during the peripartum period is a rare injury to the pelvic ring. In most cases, conservative treatment is successful. Nonetheless, there are cases where surgical intervention is necessary. We analyzed five surgical cases treated in our department and performed a literature review. Case presentations Five women, ranging in age from 25 to 38, who experienced peripartum symphysis rupture were primarily treated with a conservative approach. Patients who did not show improvement and met certain criteria, such as experiencing pain starting from childbirth, having a separation in the pubic bone of more than 10 mm, and/or having a vertical instability greater than 5 mm, were recommended to undergo surgery. The average length of time between childbirth and surgery was 5.6 months, ranging from 1 to 14 months. One patient was treated with an external fixator, another patient received a combination of an external fixator and an anterior plate, and three patients were treated with anterior plates. In four cases, we observed a failure in fixation and a partial or complete loss of reduction. The plate and screws were removed in one case, and in three cases, revision surgery was performed. One case involved using a larger plate, while the other used 90-90 plating, known as “box plate fixation.” The mean follow-up was 7.4 years. Two cases had good results, and two had excellent results on the Lindahl scale. Conclusion For patients with peripartum pubic symphyseal dislocation, our case series and literature review demonstrated that early reduction and fixation correlate with improved clinical outcomes and lower implant failure. For patients with subacute/chronic injuries, there was a higher incidence of implant failure. Orthogonal plate fixation and/or pubic symphysiodesis was associated with improved clinical outcomes.